The ultimate sales managers' guide - Klymshyn, John. (Hoboken, N.J. : Wiley, 2006)
A practical, prescriptive guide to managing a sales team The Ultimate Sales Managers' Guide provides real-world solutions to challenges faced by sales managers with all levels of experience. It addresses the most important issues facing sales managers today and offers proven guidance on all the major aspects of the job.
Hiring -- Training -- Performance evaluation -- The three-tiered sales team -- Rewards and recognition -- When to fire a salesperson -- Group meetings -- One-on-one meetings : fifteen minutes of fame -- Goals lead to greatness -- The three-step business plan -- Ten tasks today -- Cold calling -- Presentation skills -- Closing techniques all salespeople should know -- Expectation management.
Includes index.
John Wiley and Sons
Keywords: Sales management -- Handbooks, manuals, etc; Selling -- Handbooks, manuals, etc; Ventes -- Gestion -- Guides, manuels, etc; Vente -- Guides, manuels, etc; BUSINESS & ECONOMICS -- Sales & Selling -- Management; Sales management; Selling; Handbooks and manuals